Substrate integrated coaxial line design for mmWave antenna with multilayer configuration. Issue 5 (5th February 2022) - Luo, Yong; Shen, Ya; Cai, Xiang; Qian, Feng; Xu, Shugong; Cui, Hengrong; Yang, Guangli
Abstract: In the 5G communication utilizing millimeter‐wave (mmWave) band, multilayer configuration is popular for mmWave antenna with module‐level integration and high‐density design. However, multilayer construction adds several substrate layers and metallic ground layers to RF signal paths, which induces extra capacitances and inductances to the original antenna, thereby deteriorating impedance matching, and distorting radiation patterns. In this paper, we investigate the influence of multilayer structure on antenna performances, and apply substrate integrated coaxial line (SICL) design to eliminate these interferences from multilayer configuration. Equivalent circuit model of the multilayer configuration with SICL is presented and verified by simulations. A mmWave antenna unit and the 1 × 4 array in multilayer configuration with SICL design are measured. Experiments show that SICL design enables impedance matching and radiation patterns to be maintained without distortions when applying multiple layers to the mmWave antenna, validating this method. It can be applied to 5G mmWave antennas that desire multilayer construction.